Deutsche Emailwarenfabrik Oskara Schindlera w Krakowie w latach 1939-1945 (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
OSKAR SCHINDLER’S DEUTSCHE EMAILWARENFABRIK IN CRACOW 1939-1945In 1939-1945 Oskar Schindler (1906-1974) was a lessee and later the owner of the former Rekord enamel factory in the Zabłocie quarter of Cracow. Until the publication of T. Keneally’s book entitled Schindler's Ark in 1983, its hero was virtually unknown in Poland. Schindler gained world renown no earlier than 1993, when Steven Spielberg made his movie Schindler's List based on this book.During WWII Schindler significantly developed the factory, which as a plant manufacturing for the army, employed cheap labour - Jewish inmates of the Płaszów Camp. In 1943 a sub-camp of Płaszów was established at the factory. It was the Zwangsarbeitslager des SS-und Polizeiführer bei den Vereinigten Firmen Deutsche Emailwarenfabrik- NKF, Deutsches Kistenwerk- Barakenwerk Chmielewski, where inmates working in the four firms mentioned in its name were located. Workers at Schindler’s factory could expect better food and suffered much less oppressive treatment than in the main camp. This was made possible due to Schindler’s positive attitude and his contacts with various organisations providing aid to Jews, active in the General Gouvernement and in Hungary.Due to Schindler’s extensive contacts with German officials in Cracow and the Commander of KL Płaszów, Amon Goeth, his factory flourished and it was easier for him to transfer his plant and the staff working for the army to Brünnlitz in Bohemia towards the end of the war. Inmates of KL Płaszów ( approx. 700 men and 300 women), who were on the list of workers transferred to the Brünnlitz camp, were saved as a result of this transfer.